2005
DOI: 10.1080/02652030500137827
|View full text |Cite
|
Sign up to set email alerts
|

Quality of organically and conventionally grown potatoes: Four-year study of micronutrients, metals, secondary metabolites, enzymic browning and organoleptic properties

Abstract: The quality of potatoes from organic and conventional farming was investigated in this study. Tubers of eight potato varieties, organically and conventionally produced at one or two geographical sites in controlled field trials, were collected in four consecutive harvests from 1996-1999. The parameters analysed included nitrate, trace elements (As, Cd, Co, Cu, Fe, Hg, Mn, Ni, Pb, Se, Zn), vitamin C, potato glycoalkaloids, as well as chlorogenic acid, polyphenol oxidase and rate of tuber enzymic browning. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
103
5
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 27 publications
21
103
5
3
Order By: Relevance
“…Reyes et al has observed that TPC in tubers decreased with tubers growth and maturity [52]. The TPC may be affected during the development of the flesh colour (purple, violet, yellow) of potato tubers [53], due to the environmental conditions, such as longer days and cooler temperatures or fertilization [52], [54], [55]. The effect of the cultivar and the differences between yellow and purple-fleshed cultivars in TPC has been found significant.…”
Section: Resultsmentioning
confidence: 99%
“…Reyes et al has observed that TPC in tubers decreased with tubers growth and maturity [52]. The TPC may be affected during the development of the flesh colour (purple, violet, yellow) of potato tubers [53], due to the environmental conditions, such as longer days and cooler temperatures or fertilization [52], [54], [55]. The effect of the cultivar and the differences between yellow and purple-fleshed cultivars in TPC has been found significant.…”
Section: Resultsmentioning
confidence: 99%
“…For example, according to Hajšlová et al (2005), conventional and organic ecological way of cultivation caused differences in the content of chlorogenic acid, and this content is higher for potatoes grown organically without the use of fertilizer. In our field experiments, in terms of influence on the content of the TP, control treatment 2 with normal doses of nutrients N, P, K, Mg was compared with treatments without fertilization with mineral fertilizers (var.…”
Section: Effect Of Fertilizationmentioning
confidence: 99%
“…Content of total polyphenolic compounds and anthocyanins is dissimilar at different stages of tuber maturity; it is affected by different environmental conditions, e.g. longer days and lower temperatures (Reyes et al 2004), way and doses of fertilization (Kumar et al 2004, Hajšlová et al 2005 or ecological way of cultivation .…”
mentioning
confidence: 99%